2019
DOI: 10.1002/edn3.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental DNA surveys for identifying occupancy and spatial distribution of Pacific Lamprey (Entosphenus tridentatus) and Lampetra spp. in a Washington coast watershed

Abstract: Surveys of environmental DNA (eDNA) have become an important and multifaceted tool for monitoring and identifying distributions and occupancy of aquatic species. This tool is attractive because it is powerful, easy to apply, and provides an alternative to traditional field survey methods. However, validating eDNA survey methods against traditional field survey methods is warranted prior to their application. We used eDNA and electrofishing to survey 10 sites in 3 tributaries of the Chehalis River, Washington, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 72 publications
(146 reference statements)
1
14
0
Order By: Relevance
“…Nevertheless, snorkel surveys conducted in previous years suggest that in reaches where a single spawning event occurs, progeny often distribute themselves relatively evenly in pools within a few hundred meters of their natal area (B. Spence, unpublished data); thus, we are confident that the relative abundances of fish observed during our surveys serve as a reasonable proxy for reach-level differences in abundance. Our success in detecting coho salmon eDNA is consistent with those of other researchers who have found eDNA methods to be as or more effective in detecting rare fish species than traditional methods such as snorkeling or electrofishing in riverine environments (Baldigo et al, 2017;Banks et al, 2016;Evans et al, 2017;Hinlo et al, 2018;Laramie et al, 2015;McKelvey et al, 2016;Ostberg et al, 2019;Robinson et al, 2019;Sigsgaard et al, 2015;Strickland & Roberts, 2019;Wilcox et al, 2016).…”
Section: Field Methods Comparisonsupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, snorkel surveys conducted in previous years suggest that in reaches where a single spawning event occurs, progeny often distribute themselves relatively evenly in pools within a few hundred meters of their natal area (B. Spence, unpublished data); thus, we are confident that the relative abundances of fish observed during our surveys serve as a reasonable proxy for reach-level differences in abundance. Our success in detecting coho salmon eDNA is consistent with those of other researchers who have found eDNA methods to be as or more effective in detecting rare fish species than traditional methods such as snorkeling or electrofishing in riverine environments (Baldigo et al, 2017;Banks et al, 2016;Evans et al, 2017;Hinlo et al, 2018;Laramie et al, 2015;McKelvey et al, 2016;Ostberg et al, 2019;Robinson et al, 2019;Sigsgaard et al, 2015;Strickland & Roberts, 2019;Wilcox et al, 2016).…”
Section: Field Methods Comparisonsupporting
confidence: 89%
“…Our study adds to the growing body of evidence indicating that eDNA methods can be a valuable tool for detecting rare fish species in riverine environments (Baldigo et al, 2017;Hinlo et al, 2018;Ostberg et al, 2019;Robinson et al, 2019;Strickland & Roberts, 2019; among others). However, similar to previous studies, the combined results from our cage experiment and field sampling indicate that the downstream detection probabilities are significantly influenced by factors related to both DNA production (i.e., fish density) and downstream transport and degradation processes, which in turn are likely strongly dependent on local environmental conditions.…”
Section: Discussionmentioning
confidence: 66%
“…However, the majority of our study streams had sites without detections in‐between sites with detections, evidence that eDNA can degrade quickly over space. Other studies from further downstream have reported that eDNA varies along a stream, is conserved over short distances of tens of meters (Tillotson et al 2018), and degrades over longer distances (kilometers; Laramie et al 2015, Tillotson et al 2018, Ostberg et al 2019), proposing that eDNA reflects a here‐and‐now presence of local abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental DNA can detect Killer Whales Orcinus orca in seawater (Baker et al 2018), carnivores in snow (Franklin et al 2019), and fish in freshwater (Jerde et al 2011, Lacoursière‐Roussel et al 2016). Specifically, eDNA has been shown to be comparable to, or more sensitive at, detecting fish than electrofishing in streams (Wilcox et al 2016, Baldigo et al 2017, Evans et al 2017, Ostberg et al 2019), particularly when species are low in abundance (Dejean et al 2012, Pilliod et al 2013, Sigsgaard et al 2015, Itakura et al 2019). Although eDNA has been used to delimit fish distribution boundaries (Jerde et al 2011, McKelvey et al 2016, Carim et al 2019), it has yet to be evaluated empirically within the context of forest management by identifying the transition from fish to no fish in a stream network (Coble et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our study is among a growing body of literature demonstrating that eDNA can be used to monitor the presence, occurrence, and spatial extent of fish populations (Laramie, Pilliod, & Goldberg., 2015; Matter, Falke, López, & Savereide, 2018; Ostberg et al., 2019; Rees et al., 2014; Wilcox et al., 2013) and to assess river connectivity for migratory fishes (Yamanaka & Minamoto, 2016). In the case of the Elwha River, we used eDNA to assess the presence of fish in upstream areas of the watershed that were previously inaccessible due to the presence of the dams, which provides evidence that key objectives for the dam removal project (i.e., fish passage, restoring connectivity) are being met for several focal species (Peters et al., 2014).…”
Section: Discussionmentioning
confidence: 99%